Local Binary Pattern (LBP) With Application To Variant Object Detection: A Survey And Method - Karis, Mohd Safirin; Abdul Razif, Nur Rafiqah; Mohd Ali, Nursabillilah; Rosli, M. Asyraf; Mohd Aras, Mohd Shahrieel; Md Ghazaly, Mariam (Institute of Electrical and Electronics Engineers (IEEE), 2016)
-